Criteria for diagnosis of the hypoplastic aortic arch in newborns and infants - L. Prokopovych; O. Golovenko; I. Perepeka; Y. Truba; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2018)
To have a clear border between norm and pathology in order to determine in which cases the present hypoplasia is quite difficult. Therefore, from a practical point of view, the key issue is the selection of criteria on the basis of which one can speak of a clinical and prognostically significant hypoplasia of the aortic arch. The review is devoted to the analysis of modern methods for determining the hypoplasia of the aortic arch and the results of surgical treatment of this pathology.